Квадратні підвіски "Козіївка / Нова Одеса" - Володарець-Урбанович, Я.В. (Археологія, 2018)
Статтю присвячено квадратним підвіскам, що в основному походять із дніпровських скарбів першої хронологічної групи за О.О. Щегловою. Дані знахідки можна об’єднати в групу прикрас «Козіївка / Нова Одеса». Окреслено типи, хронологію та ареал поширення таких прикрас. The square pendants decorated with hemispheres in the corners and center, and rows of pressed dots pierced by a punch along the edge, with riveted ears are studied in the paper. These adornments can be joint into the group of “Koziivka / Nova Odesa” pendants type. The first type is represented on the moulds from Bernashivka and Sukha Homilsha. The second type is more numerous: these are the finds from Koziivka / Nova Odesa, Poltava (2014), Cherkasy-Konopelka and Khytsivskyi hoards on the left bank of Dnieper River, from the burial grounds Luchyste, crypt 54, layer 3, grave 16 in the Crimea and “Leninskii put” in the Ciscaucasia. The chronology of these square-shaped pendants is spread since the period of formation of the decoration of hoards of the first chronological group according to O.A. Shcheglova (second half of the 6th — middle / third quarter of the 7th century), and until the period of deposition of the hoards (second — third quarter of the 7th century). This chronology could be confirmed by the items from Luchyste burial ground: the grave 16 of crypt 54 is dated to the mid-7th century. Статья посвящена квадратным подвескам, украшенным полусферами по углам и центру, и рядами прессованных точек, выбитых пуансоном по краю, с приклепанными ушками. Данные украшения можно объединить в группу подвесок типа «Козиевка / Новая Одесса». Первый тип представлен на формочках из Бернашовки и Сухой Гомильши. Второй тип более распространен: это находки из Козиевско-Новоодесского, Полтавского (2014 р.), Черкасско-Конопельковского и Хитцовского кладов на Днепровском Левобережье, из могильника Лучистое, склеп 54, слой 3, погребение 16 в Крыму и на могильнике «Ленинский путь» в Предкавказье. Хронология бытования таких украшений входит в период формирования убора кладов первой хронологической группы по О.А. Щегловой (вторая половина VI в. — середина / третья четверть VII в.), и до периода выпадения самих кладов (вторая — третья четверть VII в.). Эту хронологию можно подтвердить находками из могильника Лучистое: погребение 16 склепа 54 датируется серединой VII ст.